A EDUCAÇÃO COMO INSTRUMENTO DE PROTEÇÃO AMBIENTAL - Maneia, Arismar; Cuzzuol, Vera (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611705642 This work relates to a reflexive action on education in formal education as an instrument oftransformation of institutional schooling behavior that concerns itself with issues about theprotection of the environment. The history of mankind drives the universe to environmentaldegradation, environmental damage caused by the rampant advancement of new technologies indifferent human activities without the sensitivity to make use of the environment and,consequently, without there being a constant environmental threat. The ideas addressedimportant posture support a broadcast about the environmental education in relation to the roleof education critical and reflective. Here if you want to demonstrate that every effort will onlyhave value when traçarmos goals for improving knowledge and awareness of environmentalcitizenship.